Collegiate involvement from an adult undergraduate perspective - Carol E. Kasworm (Adult Education Research Conference, 1995)
This current qualitative study of adult undergraduate students challenges past assumptions of effective undergraduate involvement based in substantive time commitments and collegiate role involvements. Five categories of adult student beliefs of involvement are suggested. A conceptual perspective of "adult undergraduate involvement" as situated learning through communities of practice is explored.